The Relationship of Knowledge of Prepuberty Adolescent Girls and Readiness for Menarche - Svetlanikova, Svetlanikova; Mohamad, Rini Wahyuni; Hafid, Ridha (Fakultas Kedokteran Universitas Jenderal Soedirman, 2025)
Menarche is the first menstruation which usually occurs between the ages of ten and sixteen years or at the beginning of adolescence in the middle of puberty before entering the reproductive period. The aim of this research was to determine the relationship between prepubertal adolescent girls' knowledge and readiness to face menarche at SDN 7 Tabongo, Gorontalo Regency. The research method uses quantitative research using an analytical research design with a crosssectional approach. The population in this study were all prepubertal teenage girls in grades IV, V, and VI at SDN 7 Tabongo, Gorontalo Regency who had not experienced menstruation. Sampling in this research used a total sampling technique. The number of samples used was 41 samples. The results of the research using the chi-square test obtained a p-value of 0.000 (<0.05), meaning that there is a relationship between knowledge and readiness for menarche in young women at SDN 7 Tabongo, Gorontalo Regency. Where good knowledge can certainly increase readiness in facing menarche. It is hoped that this research can provide input for nurse practitioners in providing education about readiness for menarche.